In vitro Transdermal Delivery of Metformin from a HPMC/ PVA Based TDS-patch at Different pH - Jahan, L.; Ferdaus, R.; Shaheen, S. M.; Sultan, M. Z.; Mazid, M. A. (Journal of Scientific Research, 2011)
In order to evaluate the pHs effect on the transdermal drug delivery, HPMC/PVA based TDS-patch was prepared. In vitro transdermal dissolution was performed at 32 oC at different pHs. Comparatively higher release rate was found in case of pH 7.4 than those of others. pHs 5.4 and 8 showed almost the same release pattern. The release fashion was Higuchi type of diffusion controlled release. This result showed that neutral pH would accumulate the maximum drug from such a TDS patch, where the skin pH (around 5.4) does not support such a release. Sustained release of drug from such a patch prefers skin pH rather than neutral pH. Keywords: Transdermal drug delivery; Higuchi diffusion; Release rate; Metformin. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7422 J. Sci. Res. 3 (3), 661-667 (2011)